2015
DOI: 10.1038/ng.3452
|View full text |Cite
|
Sign up to set email alerts
|

The noncoding RNAs SNORD50A and SNORD50B bind K-Ras and are recurrently deleted in human cancer

Abstract: Small nucleolar RNAs (snoRNAs) are conserved noncoding RNAs best studied as ribonucleoprotein (RNP) guides in RNA modification1,2. To explore their role in cancer, we compared 5,473 tumor-normal genome pairs to identify snoRNAs with frequent copy number loss. The SNORD50A-SNORD50B snoRNA locus was deleted in 10–40% of 12 common cancers, where its loss was associated with reduced survival. A human protein microarray screen identified direct SNORD50A and SNORD50B RNA binding to K-Ras. Loss of SNORD50A and SNORD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 31 publications
7
143
0
Order By: Relevance
“…Whereas snoRNAs of the C/D box family are well-known to guide fibrillarin-mediated 2′O methylation of the ribosomal RNA, reduced expression and both somatic and germ line mutations in U50 have been reported from breast and prostate cancer3031. Furthermore, a non-canonical function of the U50 snoRNA in modulating RAS activity was recently described32. Although currently unclear, this is likely independent from the SNHG5 mechanism characterized in this paper.…”
Section: Discussionmentioning
confidence: 63%
“…Whereas snoRNAs of the C/D box family are well-known to guide fibrillarin-mediated 2′O methylation of the ribosomal RNA, reduced expression and both somatic and germ line mutations in U50 have been reported from breast and prostate cancer3031. Furthermore, a non-canonical function of the U50 snoRNA in modulating RAS activity was recently described32. Although currently unclear, this is likely independent from the SNHG5 mechanism characterized in this paper.…”
Section: Discussionmentioning
confidence: 63%
“…For example, emerging data suggest that snoRNAs may contribute to alternative splicing, 7 regulation of chromatin structure, 8 metabolism, 9 and neoplastic transformation. 10 The contribution of snoRNAs to the regulation of normal and malignant hematopoiesis is largely unknown. Chu et al reported that overexpression of the H/ACA box snoRNA ACA11 in t(4;14)-associated multiple myeloma contributes to myeloma cell proliferation and resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although SNORDs are considered housekeeping genes, the expression of some SNORDs is altered in cancer. For example, changes in the expression of SNORD27, -30, -25, and -31 mark the progression of smoldering multiple myeloma (21), and SNORD50 deletions are associated with prostate and breast cancer (22)(23)(24). Genome-wide comparison of SNORD expression between cancer and normal cells showed the presence of two classes of SNORDs that differ in their terminal stems but are made from the same SNORD hosting intron (25).…”
mentioning
confidence: 99%